Issues of Philosophical Anthropology Resulting from the Impact of Biotechnology on Human Nature - Paul Rohan, J.C. (Sri Lanka National Seminary Journal, 2011)
The title in discussion has two areas: philosophical anthropology and biotechnology. Both are new areas in the field of knowledge; however, chronologically the former precedes the latter. Biotechnology is a recent phase of the technological revolution. The advancement of scientific knowledge has made possible sophisticated modes of technical intervention on the physical constitution of humans as well as on animals, vegetation and the environment in general. Modern technology has yielded new information on the structure and operation of organic life and made possible artificial intervention on organisms in general, and on humans in particular, in a way that was only hypothetical some decades ago. This intervention has unleashed experimentation, not only therapeutic, on the structures of organic life. It is another sign that technocratic culture has affected every sphere of life, reducing life to mere mechanical motion. Biotechnology is the most ambitious dream of homo faber which aims at modifying the organisms. In the order of presentation of the article, therefore, a brief exposition of both will occur together with an explication of how the impact of biotechnology on human nature creates issues and concerns in the field of philosophical anthropology.
Keywords: Homo Faber; Anthropocentric; Noumena; Besouled Organism; Artificial Intervention; Manipulate